ANALYSIS OF THEMATIC LEARNING IN THE 2013 CURRICULUM SDN 7 KEBUMEN - Teguh Rahayu; Kurnia Wardani Putri; Isnaeniatun Umifaiqoh; Kartika Chrysti Suryandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The policy of applying the 2013 curriculum has an impact on the implementation of thematic learning. This study aims to describe the application of thematic learning in SDN 7 Kebumen. This study uses descriptive qualitative methods. The subjects of this study were teacher of class I and teacher of class IV, 5 studens of class I and 5 students of class  IV. The students were taken from students with high, medium and low abilities. Data collection techniques are carried out through observation, interviews, and questionnaires. Data analysis techniques used are source triangulation and technical triangulation The results of this study prove that the application of thematic learning has been running in accordance with the 2013 curriculum, teachers and students respond well to the application of thematic learning. But there are still a few obstacles. Among them are apperception and motivation are less memorable for students. Thus, it can be concluded that the implementation of thematic learning class I and IV in SDN 7 Kebumen is in accordance with the 2013 curriculum, but there needs to be an increase in apperception and motivation.